Determining factors of selection among international guests & interrelated of purpose of visit and nationality, a study on five stars hotel in Kota Kinabalu / Muhid Hassan - Hassan, Muhid (2012)
The purpose of this study are two, first is to asses the cross-interrelated of nationality and purpose of visit of international guests in Kota Kinabalu and to examine the factors that significant to five stars hotel selection among international guests towards five stars hotel in Kota Kinabalu. The population of this study are the international guests that come and stayed in five stars hotel in Kota Kinabalu. The subject was provided with structured questionnaire that was design based on likert scale approach. Reliability and linear regression analysis were used as to find the most significant factor of selection of international guests towards five stars in Kota Kinabalu. The international guests has made their selection that brand equity become the most influential factor for them to chose for a five stars hotel in Kota Kinabalu. Moreover, most of the international guests that come and stayed in five stars hotel in Kota Kinabalu are from Asian region which lead by China, Singapore and Japan. Therefore the finding is meaningful as it will be valuable information for five stars hotelier in Kota Kinabalu to further design their business strategy. The researcher found a limitation of selecting the most significant variables that will give a strong relationship towards the factor of selection in this study. This study indicates the main factor of selection derived from international guests that come and stayed in five stars hotel in Kota Kinabalu. This study also tried to highlight the interrelated importance of international guests' nationality and their factor of selection towards five stars hotel in Kota Kinabalu.